Regenerative Agriculture and its Prospects in Nepal: A Review - Das, Soni Kumari; Karki, Tika Bahadur; Gyawaly, Pankaj; Neupane, Reshama; Bhattarai, Rajendra Kumar; Kaduwal, Sangita; Chaulagain, Bhimsen (Agronomy Journal of Nepal, 2022)
Modern agriculture is heavily dependent on soil. Soil’s carrying capacity is being decreased these days due to erosion, depletion of soil nutrients and climate change. Regenerative agriculture is a way of farming both plants and animals that enriches and restores topsoil, and in turn, improves the water cycle. Nepal is also facing the ill effects of the conventional agriculture system. Therefore, an attempt has been made in this review article to highlight some of the alternative production systems suitable for Nepal. The findings of this review paper were about regenerative agriculture technology reduced the cost of production through minimum tillage, less use of agriculture inputs, less labor, consumption of less irrigation, maintaining soil moisture, water holding capacity and nutrient value through crop residue, crop rotation, soil cover, reduced soil erosion and run off top layer soil and increases the soil fertility through soil carbon sequestration that mitigates the climate change effects. The major constraints of regenerative agriculture are the lack of appropriate information and technologies in hand. For policymakers, farmers and food processing and marketing companies, regenerative agriculture has been an alternative production system with lower impacts on the environment. Therefore, to promote the identified and developed regenerative agricultural practices, participatory research in the farmer’s field with large-scale demonstration across the egro-ecological domains of the country.